Fruit and vegetable intake in 7-9-year-old children. Effect of a school-based intervention on fruit and vegetable intake at school and at home - Erna Héðinsdóttir 1976- (2010)
Objective: To further explore the effects of the school-based intervention “Nutrition in Icelandic 7 – 9 - year-old children” on fruit and vegetable intake in the midmorning-break, in the school-lunch and at home. Gender difference was explored and the effects on those children with lowest levels of fruit and vegetable intake, at baseline, versus those with the highest level. Design: School-based dietary intervention study on fruit and vegetable intake in 7 – 9 -year-old children, assessed with three-day weighed dietary records. Setting: Six randomly selected schools in Reykjavik, Iceland. Three intervention schools and three control schools. Subjects: 7 – 9 -year-old school children. 163 children were studied for baseline values, and 105 for comparison of baseline and follow-up fruit and vegetable intake. Results: The highest proportional increase, 65% (P=0.047), in fruit intake was in the midmorning-snack but increase in vegetable intake was more evenly distributed. Boys in the intervention group increased their fruit intake by 61 g/day (P=0.001) in the midmorning-snack and the girls in the control group decreased their fruit intake by 72 g/day (P<0.001) in the midmorning-snack. The lowest tertile in the intervention group increased its schoolday fruit and vegetable intake by 109 g/day (P<0.001) and the highest tertile in the control group decreased its intake by 256 g/day (P=0.028). Conclusion: Intervention and/or multi component nutritional education in schools are very effective in sustaining and improving fruit and vegetable intake in school-children. Most changes in intake from the present intervention are seen in the midmorning-snack. Rannís - The Icelandic Centre for Research The city of Reykjavik The Ministry of Education, Science and Culture Brim Seafood World Class Health Clubs